Critical Discourse Analysis of Vladimir Putin's Political Speech (2018) - Puspita Puspita; Al Farauqi; Sunarti Sunarti (Budapest International Research and Critics University, 2022)
This research aims to find out the out the language choice, the ideology, and the power of Putin in delivering his speech. The researcher used documentation to collect the data. The data of this research was all the utterances of the speech of Putin in 2018. The method used in this research was Critical Discourse Analysis by Norman Fairclough. The result of this research found that Putin used ‘colleague” to greet his audiences and to make his audiences feel that they are in the same position. The other result was Putin used an ideology that puts the people first concern. The power relationship is also found in this research. It can be seen that Putin mentioned that all achievement was not only his effort but there was the hard work of all parties. It can be concluded that Critical Discourse Analysis can be used as a method to identify the language.